Boredom proneness and fear of missing out mediate relations between depression and anxiety with problematic smartphone use. Issue 1 (12th July 2019) - Wolniewicz, Claire A.; Rozgonjuk, Dmitri; Elhai, Jon D.
Abstract: Depression and anxiety severity are found in numerous studies to correlate with increased levels of problematic smartphone use. Yet there are less available data on other psychopathology‐related correlates of such use. Two potentially important variables related to depression and anxiety, and recently found related to problematic smartphone use severity, are boredom proneness and the fear of missing out (FOMO). Our aims were to (a) assess boredom proneness and FOMO in relation to problematic smartphone use severity and (b) assess the mediating roles of boredom proneness and FOMO in relationships between depression/anxiety severity with problematic smartphone use severity. We recruited 297 American college students for a web survey, assessing constructs including FOMO, boredom proneness, depression, anxiety, problematic smartphone use, and smartphone use frequency. We tested a structural equation model to assess relations between depression and anxiety severity with boredom proneness and FOMO, and relations between these psychopathology constructs with levels of smartphone use frequency and problematic use. Results demonstrate that FOMO was significantly related to problematic smartphone use severity. FOMO also mediated relations between boredom proneness and problematic smartphone use severity. Furthermore, boredom proneness and FOMO serially mediated relations between both depression and anxiety severity with problematic smartphone use severity. Results are discussed in the context of Compensatory Internet Use Theory and the I‐PACE model in understanding factors driving problematic smartphone use.